Why should custody and education be abolished?. (2nd January 2016) - He, Haibo
Abstract : Developed in cracking down prostitution and whoring, Custody and Education is an administrative compulsory measure that long restricts freedom of person. With the 1991 Decision of the Standing Committee of the National People's Congress on Strictly Prohibiting Prostitution and Whoring as its basis, Custody and Education does not contravene the principle of law reservation, and is therefore currently valid by statute. However, the Custody and Education system has become a dark corner of the rule of law and human rights in China, due to the lack of limitation on the law's application and due process, insufficient judicial remedy as well as rigid and sometimes violent management at Custody and Education centers. As a result, the Custody and Education system is not constructive to social conduct, and it impairs social justice since it has, in practice, degenerated into a punitive measure mainly against the population of prostitutes and prostitute visitors with low socio-economic status. The Custody and Education system does little to rehabilitate prostitutes, fails to deter the act of prostitution and whoring, and is unnecessary for the examination and treatment of sexually transmitted diseases. The Custody and Education system has lost its legitimacy in general and thus ought to be abolished. Local law enforcement agencies' dispiritedness and the general public's antipathy destine its termination.